ChemInform Abstract: Selenium Dioxide—Mediated Synthesis of Fused 1, 2, 4‐Triazoles as Cytotoxic Agents. Issue 17 (April 2016) - Zheng, Heng; Wang, Kang; Zhang, Wei; Liu, Ruihuan
Abstract: Title compounds are prepared by oxidative intramolecular cyclization of several alkyl and aryl hydrazones in the presence of selenium dioxide.